Enzymatic production of multifunctional bioactive peptides from sea cucumber (Actinopyga lecanora Jaeger) - Ghanbari, Raheleh (2014)
Food protein-generated bioactive peptides are natural products that have nutraceutical and pharmaceutical properties. They have been reported to have antioxidative, anti-bacterial, anti-hypertensive and anti-inflammatory properties. Due to their potential, there is an increasing interest in the use of these peptides for general health maintenance and well-being. Sea cucumbers have been utilized as a folk remedy to cure some diseases in some Asian countries for decades. Among the species, Actinopyga lecanora, commonly known as stone fish was chosen due to its relatively high protein content (58.30%). Moreover, it is considered as a by-catch of the Malaysiaʼs fishing industry. This study was targeted to generate multifunctional bioactive peptides against cardiovascular diseases and its risk factors (hypertension and oxidative stress), inflammation and microbial infections, from an edible species of sea cucumber through enzymatic proteolysis. Thus, the protein was proteolysed using six proteases namely alkalase, papain, bromelain, flavourzyme, pepsin, and trypsin under their optimum conditions for 24 h. The degree of proteolysis and peptide content were evaluated using O-phthaldialdehyde based on a spectroscopic method. The amino acid compositions of A. lecanora and its generated proteolysates were evaluated. The multifunctional activities of the A. lecanora generated proteolysates including anti-hypertensive, anti-oxidative, anti-bacterial and inhibition of nitric oxide (NO) activities were determined. The anti-oxidative activity was measured using DPPH• radical scavenging and ferrous-ion chelating activities. The anti-bacterial activity was measured as growth inhibition (%) against Pseudomonas aeruginosa, Pseudomonas sp., Escherichia coli and Busilus subtilis and Staphylococcus aureus. The inhibition of NO-production was evaluated using Griess assay in RAW 264.7 cells. The bromelain-generated proteolysate showed the highest multifunctional activities after 1 h of proteolysis. The abilities of proteolysate to inhibit ACE, scavenge DPPH free radicals and chelate iron (Fe2+) were 48.80%, 40.00% and 30.24%, respectively. The potency of proteolysate to inhibit NOproduction in RAW 264.7 cell was 60.02%. Subsequently, this proteolysate showed the highest anti-bacterial activities against Pseudomonas sp., P. aeruginosa, E. coli and S. aureus of 51.85, 30.07, 30.00 and 24.30%, respectively. The proteolysate was further profiled by fractionation methods based on hydrophobicity using RP-HPLC and isoelectric properties using isoelectric focusing technique. The best fraction in terms of multifunctional properties was selected for peptide identification and sequencing using an UPLC-QTOF-MS system, where a total of 12 peptides were identified. The multifunctional activities of the identified peptides were studied. Based on the results obtained 3 peptides namely LREMLSTMCTARGA, VAPAWGPWPKG and ATSFREALRCGAE showed the strongest ACE inhibitory activities of 98.10, 95.23 and 59.95%, radical scavenging activity of 93.30, 70.44 and 78.20% and ferrous ion chelating activity of 57.00, 43.50 and 54.00%, respectively. NO-production was inhibited by these peptides with values of 76.30, 69.90 and 30.00% and their NO scavenging activities were 51.14, 50.32 and 34.85%, respectively. These peptides exhibited growth inhibition against P. aeruginosa, Pseudomonas sp., E. coli and S. aureus with values ranging from 50.00 to 75.30%. The effect of the proteolysate and its derived peptides on the viability of RAW 264.7 cells were evaluated using MTT assay. Results showed that these samples had no cytotoxic effect and the cell viability was higher than 90%. Kinetic studies of ACE inhibition of multifunctional peptides demonstrated un-competitive and mixed-mode patterns. Results showed that A. lecanora could be used as an economical protein source to generate invaluable multifunctional proteolysate and bioactive peptides which could be exploited in the formulation of various functional foods or used as a source of nutraceuticals.